Enhancing Moral Values through Quran Recitation Activities in Junior High School - Prasetyo, Oky Bagas; Yulianto, Yulianto; Munir, Muhammad Mubasysyir (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2024)
The social phenomena arising among teenagers today, such as brawls, immoral actions, and similar issues, stem from a lack of moral education among youth. This situation is exacerbated by the fact that fewer teenagers adhere to the teachings of the Qur'an, as they often prefer reading novels or comics that may contain elements of violence and pornography, distancing them further from the goals of Islamic education. Therefore, this thesis will discuss enhancing moral education through a Qur'an recitation program at MI Miftahul Ulum Disanah, Sampang Madura. This study is significant because children are the hope of their parents, society, religion, and the nation. This research employs a qualitative method to describe or illustrate the actual phenomena at the research site. Data collection techniques include observation, interviews, and documentation. To organise the results systematically, the researcher will analyse the data through data reduction, presentation, and verification (conclusions). From the analysis, it can be determined that the improvement of moral education at MI Miftahul Ulum Disanah, Sampang Madura, is implemented through habituation, role modelling, practice, memorisation, and assignment. These activities function well, as evidenced by the graduates who can read and write the Qur'an and perform Sunnah prayers, which they apply daily. Other efforts made by educators to enhance moral education among children include: for teachers, improving the quality of teachers and holding meetings with them; for students, involving them in religious activities, guiding them with Islamic readings, instilling habits of worship, conducting extracurricular activities such as Qira'ah, calligraphy, and Islamic holidays, teaching the fundamental values of religion through subjects like Aqidah, Akhlaq, Tauhid, Tarikh, and others, and providing good examples for the students.